반투명 페로브스카이트 태양전지용 투명전극 소재 - 이필립(Phillip Lee); 고민재(Min Jae Ko) (Current Photovoltaic Research, 2018)
Recently, perovskite solar cells have shown tremendous improvement in power conversion efficiencies. Moreover, they have potential in semitransparent solar cell applications due to their high absorption coefficients. In order to fabricate semitransparent perovskite solar cells with good performance, it is essential to consider the suitability of transparent electrode materials in various aspects, such as transparency, conductivity and fabrication process. In this review, candidate materials for transparent electrodes in perovskite solar cells including carbon-based nanomaterials, conductive polymers and metallic nanostructures are discussed.